New aryloxybenzylidene ruthenium chelates – synthesis, reactivity and catalytic performance in ROMP - Żak, Patrycja; Rogalski, Szymon; Majchrzak, Mariusz; Kubicki, Maciej; Pietraszuk, Cezary (Beilstein Journal of Organic Chemistry, 2015)
New phenoxybenzylidene ruthenium chelates were synthesised from the second generation Grubbs catalysts bearing a triphenylphosphine ligand (or its para-substituted analogues) by metathesis exchange with substituted 2-vinylphenols. The complexes behave like a latent catalyst and are characterized by an improved catalytic behaviour as compared to that of the known analogues, i.e., they exhibit high catalytic inactivity in their dormant forms and a profound increase in activity after activation with HCl. The strong electronic influence of substituents in the chelating ligand on the catalytic activity was demonstrated. The catalytic properties were tested in ROMP of cyclooctadien (COD) and a single selected norbornene derivative.
Keywords: chemoactivation; latent catalysts; metathesis; ROMP; ruthenium